The making of the professional manager - Denny, Richard; Lake, Nick; Turner, Barry; Gawith, Paul ([S.l.] : Man Management Ltd. [production company] ; Kuala Lumpur : First Training [distributor], 1987)
The making of how to manage people. How to be a good manager and a professional manager.
Camera, Mark Lipscomb ; sound supervisor, Bill Cadman ; lighting director, Nigel Fisher
Keywords: Executives -- Training of; Management; Executives -- Conduct of life